Research on Fiber Bragg Grating (FBG) Sensor: Strain and Temperature Measurements - Mahadi, Nur Hidayah (Universiti Teknologi PETRONAS, 2017)
Strain and temperature measurements are very important parameters to analyze the deformation of the soil specimen. Triaxial test is the most common and established instrumentation testing used to determine the mechanical properties of the soil specimen. However, limitations of electric instruments in triaxial test such as electromagnetic interference, signal loss, less stable and low resolution can create an error in strain measurement. Fiber Bragg Grating (FBG) sensor is introduced in monitoring field with numerous advantages compared to conventional sensing technology. Its outstanding advantages are small sized and lightweight, immune to electromagnetic interference, long term stability, good corrosion resistance, very low magnetic field interactions, and ease of installation (time, cabling, and testing). This technology has been recognized and successfully monitored for measuring various physical quantities such as displacement, pressure and acceleration.